MEANING CONSTRUCTION OF SLOGANS USED BY THE PRESIDENT CANDIDATES IN THE GENERAL ELECTION (PEMIRA) UB 2011 - ASHARI, AFIF (Jurnal Ilmiah Mahasiswa FIB, 2015)
Keywords: Discourse Analysis, Critical Discourse Analysis, Slogan, General Election (PEMIRA) UB 2011. This research is about the analysis of Critical Discourse Analysis of the slogan used by the president candidates of Brawijaya University on general Election (PEMIRA) in 2011 by using Fairclough model of CDA. The researcher investigated two research problems, namely: (1). What are the lexical and structural meaning of construction in the slogans of president candidates in PEMIRA UB 2011 and (2). What are the social impacts of the slogans meaning of president candidates in PEMIRA UB 2011 toward the students at Universitas Brawijaya reflected on the image of perfect leader.This research used qualitative approach. The primary data were the slogans from two president candidates in General Election (PEMIRA) UB 2011. The supporting data were derived from articles on PEMIRA UB 2011. In addition, the researcher also used interviews with both of president candidates of Universitas Brawijaya in PEMIRA UB 2011 in order to complete this study.The results of this study showed that there were 7 slogans used in the general election (PEMIRA) UB 2011. Based on the text analysis on the slogans, the use of words such as commitment, aspirations have big impact towards the public opinion. It could influence public’s view to the figure of president candidates that it does not come out as a "stereotypical" an ordinary general election. The role of social media is important as slogans can also serve as “boomerang” that can decrease the belief of the voters. This condition obviously influences the psychological felling of the voters that they can easily believe those issues and automaticlly choose other candidate. The social effect on the use of slogan president candidates for the winner can be seen in everyday life. The winner often gets many privileges in the society and their group. Furthermore, the slogan has a role that less than supporting role and organization background of the president candidates in terms of influencing the reader or voters.Finally, the use of the slogan of president candidates had influenced the supporters and student at the time. It can be seen when Fandi becomes the winner in general election (PEMIRA) UB 2011. The researcher suggests for the future researcher to enrich the field of this study by possibly exploring other numerous object with different theory for CDA. Moreover, it can be about CDA containing a critical thinking which in fact is very helpful for students to explore more about a subject given whether they will accept it or not.